2007
DOI: 10.1038/sj.leu.2404593
|View full text |Cite
|
Sign up to set email alerts
|

Divergent cytotoxic effects of PKC412 in combination with conventional antileukemic agents in FLT3 mutation-positive versus -negative leukemia cell lines

Abstract: FMS-like tyrosine kinase-3 (FLT3) is a new therapeutic target for acute myelocytic leukemia (AML), because FLT3 mutations are the most common genetic alterations in AML and are directly related to leukemogenesis. We studied cytotoxic interactions of a FLT3 inhibitor, PKC412, with eight conventional antileukemic agents (cytarabine, doxorubicin, idarubicin, mitoxantrone, etoposide, 4-hydroperoxy-cyclophosphamide, methotrexate and vincristine) using three leukemia cell lines carrying FLT3 mutations (MOLM13, MOLM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 38 publications
3
41
0
Order By: Relevance
“…Interestingly, combinations with standard cytotoxic drugs used in RMS treatment showed only minimal synergistic effects. This is in contrast to acute myeloid leukaemia (AML) for which PKC412 is currently evaluated in phase II clinical trials, as combinations with conventional antileukemic agents demonstrate superior anti-cancer activity for FLT3 mutation-positive AML compared to single treatment alone (Furukawa et al, 2007). Only one study in AML suggested that HDAC inhibitors could be used effectively in combination with PKC412 (Bali et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, combinations with standard cytotoxic drugs used in RMS treatment showed only minimal synergistic effects. This is in contrast to acute myeloid leukaemia (AML) for which PKC412 is currently evaluated in phase II clinical trials, as combinations with conventional antileukemic agents demonstrate superior anti-cancer activity for FLT3 mutation-positive AML compared to single treatment alone (Furukawa et al, 2007). Only one study in AML suggested that HDAC inhibitors could be used effectively in combination with PKC412 (Bali et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that PKC412 has synergistic effects with most antileukemic agents for FLT3-mutated leukemia cell lines (Furukawa et al, 2007). In contrast, PKC412 is antagonistic to most drugs, except for those inducing mitotic arrest or active in the G 2 /M phase in leukemia cell lines without FLT3 mutations.…”
Section: Introductionmentioning
confidence: 98%
“…Inhibitors of histone deacetylase, proteasome and Bcl-2 antisense oligonucleotides have also been used as targeted drugs in the clinical treatment of AML (12). Furthermore, inhibitors of Fms-like tyrosine kinase 2 (FLT-2), such as lestaurtinib (CEP701), tandutinib (MLN518) and PKC412 have shown benefit in treating FLT3-associated AML (13).…”
Section: Introductionmentioning
confidence: 99%